Radar Mapping Using Sinsgle Images, Stereo Pairs and Image Blocks Mathods and Applications - W. Leberl, Franz (Revista Brasileira de Cartografia, 1978)
The present state of mapping with radar is reviewed. Emphasis is on radargrammetric mapping with single images, stereo pairs and block adjustment. Applications to thematic mapping will be addressed as well. Examples presented concern radar mosaicking, sea-ice study and extra-terrestrial mapping (Moon, Venus).